1996
DOI: 10.2307/2269378
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Acidification of Small Streams in the Northeastern United States: Ionic Controls of Episodes

Abstract: As part of the Episodic Response Project (ERP), we intensively monitored discharge and stream chemistry of 13 streams located in the Northern Appalachian region of Pennsylvania and in the Catskill and Adirondack Mountains of New York from fall 1988 to spring 1990. The ERP clearly documented the occurrence of acidic episodes with minimum episodic pH ≤ 5 and inorganic monomeric Al (Alim) concentrations > 150 μg/L in at least two study streams in each region. Several streams consistently experienced episodes with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
123
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(128 citation statements)
references
References 32 publications
5
123
0
Order By: Relevance
“…As in some other areas where similar methods have been applied (e.g. Evans et al, 1995;Wigington et al, 1996), this analysis suggests that, while long-term elevated mean SO 4 concentrations are the dominant cause of chronic acidification at the stream, short-term variability in SO 4 (between high-and low-pH conditions) is typically quite small. Therefore, variations in ions other than SO 4 must account for most of the short-term variation in ANC.…”
Section: Resultssupporting
confidence: 63%
“…As in some other areas where similar methods have been applied (e.g. Evans et al, 1995;Wigington et al, 1996), this analysis suggests that, while long-term elevated mean SO 4 concentrations are the dominant cause of chronic acidification at the stream, short-term variability in SO 4 (between high-and low-pH conditions) is typically quite small. Therefore, variations in ions other than SO 4 must account for most of the short-term variation in ANC.…”
Section: Resultssupporting
confidence: 63%
“…Trout abundance was reduced and acidsensitive fish were absent from streams with median pH Ͻ5. (Wigington et al 1996). Baker et al (1996) concluded that atmospheric deposition contributed to the severity of episodes in the streams, and that episodic acidification can have long-term effects on fish communities in small streams.…”
Section: Toxicity Of Surface Watersmentioning
confidence: 99%
“…High discharge can also cause acid episodes (Mulder et al, 1995). In the late 1980s the United States Environmental Protection Agency (US EPA) conducted a comprehensive project (Episodic Response Project) on acid episodes in 13 streams in the northeastern United States (Wigington et al, 1996).…”
Section: Introductionmentioning
confidence: 99%